2021
DOI: 10.1002/jsfa.11379
|View full text |Cite
|
Sign up to set email alerts
|

Effect of parboiling conditions on zinc and iron retention in biofortified and non‐biofortified milled rice

Abstract: BACKGROUND Zinc‐biofortified rice could contribute to zinc intake in deficient populations, but processing it into parboiled rice could affect this potential benefit. Zinc and iron true retention (TR) in milled rice produced under conditions resembling household and commercial parboiled methods was evaluated. Zinc and iron TR in milled rice obtained from biofortified and non‐biofortified rice subjected to different soaking temperatures during parboiling was also evaluated. RESULTS Conditions resembling commerc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Parboiled rice is also preferred in Bangladesh due to its longevity (less spoilage), digestibility, and reduced stickiness (Jaim & Hossain, 2012). While zinc is contained in the endosperm of the grain and, therefore, is mostly protected during milling, this is not the case if paddy rice is first parboiled (Taleon et al., 2022). During parboiling, zinc moves from the endosperm towards the kernel bran, making it more vulnerable to removal during milling (Taleon et al., 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Parboiled rice is also preferred in Bangladesh due to its longevity (less spoilage), digestibility, and reduced stickiness (Jaim & Hossain, 2012). While zinc is contained in the endosperm of the grain and, therefore, is mostly protected during milling, this is not the case if paddy rice is first parboiled (Taleon et al., 2022). During parboiling, zinc moves from the endosperm towards the kernel bran, making it more vulnerable to removal during milling (Taleon et al., 2020).…”
Section: Introductionmentioning
confidence: 99%
“…In a recent study conducted in Bangladesh, zinc concentration was measured for parboiled rice at the low‐milling level of 8% (to remove most of the pericarp and germ), and the highest milling level of 16% which produces white rice. The analysis showed that the low‐milled grain had up to 77% more zinc than the highly milled grain and when combining the zinc content increase through biofortification and low‐milling, biofortified low‐milled rice had up to 156% higher zinc content than non‐biofortified high‐milled rice (Taleon et al., 2022). In addition to zinc loss, other vitamin and micronutrients are also lost during a high degree of milling (Muthayya et al., 2014).…”
Section: Introductionmentioning
confidence: 99%